EFFECT OF PEER GROUP NUTRITION EDUCATION AMONG SCHOOL GOING ADOLESCENT GIRLS IN THOOTHUKUDI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Adolescents are considered to be a nutritionally vulnerable segment of the population. A rapid growth rate combined with a marginal nutrient intake increases the risk of nutritional deficiencies in this population. Healthy diets and adequate regular physical activity are major factors in the promotion and maintenance of good health during adolescence and throughout the entire life course. The phenomenal growth that occurs in adolescence creates increased demands for energy and nutrients. The need of nutrition education is to determine strategies to prevent the occurrence of under nutrition, anaemia and over nutrition among school going adolescents in order to increase their nutritional status and to enable them to grow into complete individuals, with mental as well as physical wellbeing. Adolescents are the future generation of any country. Their nutritional needs are critical not only for the wellbeing of a society, but their health has been neglected because they are considered to be less vulnerable to diseases compared to relatively young children or the old people. If the adolescents are well-nourished, they can make optimal use of their skills, talents and energies and would be healthy and responsible citizens (Priyadharshiniet al., 2011).